Humble leadership : the power of relationships, openness, and trust - Schein, Edgar H.; Schein, Peter A. (Berrett-Koehler Publishers, 2018)
This book explores the idea of a reimagined form of leadership that coincides with emerging trends of relationship building, complex group work, diverse workforces, and cultures in which everyone feels psychologically safe.